Reconceptualization of Marriage Dispensation Provisions In Religious Courts (Solution To Reduce The Number of Early Marriages In Indonesia) - Hasanah, Uswatun; Syahnan, Mhd; Tanjung, Dhiauddin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: In the Marriage Act has been formulated several principles of marriage, one of which is the principle of marriage in terms of age of marriage. In accordance with the provisions, it is confirmed that the age of marriage for men and women is 19 (nineteen) years. Furthermore, if there are irregularities regarding the parties who have not reached the specified age, it is permissible to apply for a marriage dispensation to the Religious Court.Purposes of the Research: This study aims to determine and analyze the rules of the game in terms of marriage in which to conceptualize the provisions of the marriage dispensation with the aim of reducing early marriage in Indonesia.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: The problem of early marriage is usually included in the category of children where the child is someone who is not yet eighteen years old, including children who are still in the womb. Therefore, it is necessary to consider the physical and spiritual maturity that makes it possible to carry out her duties as a wife and as a mother as well as possible, if it is used as the best benchmark for a daughter to carry out a marriage. in accordance with the circumstances in Indonesia the lowest limit for a girl is 18 years.